Minimally invasive endoscopic surgery for treatment of spontaneous intracerebral haematomas - Beynon, Christopher; Schiebel, Patrick; Bösel, Julian; Unterberg, Andreas; Orakcioglu, Berk (Neurosurgical review, 2015)
Spontaneous intracerebral haemorrhage (ICH) is a devastating disease with a mortality rate of more than 40 % and a high morbidity rate with 10-15 % of survivors remaining fully dependent [11]. The role of surgical treatment of ICH remains a matter of controversy and ongoing investigation. Advances in neurosurgical techniques such as endoscopy and neuronavigation have been established in various fields of neurosurgery. Results of reported case series have suggested that some patients with ICH may benefit from haematoma evacuation through minimally invasive endoscopic procedures. In this article, we focus on the pathophysiologic rationales behind minimally invasive haematoma evacuation through endoscopic surgery and provide an overview of technical developments and reported patient series. In addition, the modalities of the surgical procedure at the authors’ institution are described. Controlled clinical trials are needed to evaluate the full potential and limitations of this promising technique.
Gesehen am 29.03.2017